Positive association between the neutrophil percentage-to-albumin ratio and constipation: a retrospective cross-sectional study - Shu, Yuping; Chen, Zuqing; Lu, Minyuan; Mi, Nai; Wan, Yong; Shen, Wei; Sheng, Zewei; Tao, Hongwu; Liu, Xuefeng; Liu, Yuedong (Frontiers in Medicine, 2025)
IntroductionThe neutrophil-to-albumin ratio (NPAR), a novel marker of systemic inflammation, has been utilized to predict outcomes in patients with cancer and cardiovascular diseases. Since inflammation plays a critical role in the pathogenesis of constipation, understanding its connection to NPAR is essential. However, the association between NPAR and constipation remains unclear. This study aims to investigate the potential relationship between NPAR and constipation.MethodData from the 2009–2010 National Health and Nutrition Examination Survey (NHANES) were utilized for this study. The neutrophil-to-albumin ratio (NPAR) was calculated as the ratio of the neutrophil percentage to serum albumin levels. To investigate the relationship between NPAR and chronic constipation, various statistical methods were applied, including interaction tests, subgroup analyses, and curve fitting techniques.ResultsAmong the 5,011 participants included in the analysis, 366 (7.30%) were identified as having chronic constipation. Higher NPAR levels were significantly associated with an increased likelihood of chronic constipation (OR = 1.05, 95% CI: 1.01–1.10, p < 0.05) based on a fully adjusted multiple logistic regression model. Further adjustments revealed that participants in the highest tertile of NPAR had an odds ratio of 1.31 (95% CI: 1.00–1.72, p < 0.05) for chronic constipation compared to those in the lowest tertile. Subgroup analyses indicated no significant association in most groups. However, a positive relationship between NPAR and chronic constipation was observed in specific subgroups, including individuals of Other Hispanic ethnicity, smokers, those with heart disease, alcohol consumers, diabetics, and those who were never married.ConclusionThis study identified a significant positive association between NPAR and the prevalence of chronic constipation. These findings suggest that NPAR may serve as a potential inflammatory biomarker for chronic constipation. Further prospective research is necessary to clarify the long-term implications of elevated NPAR levels on chronic constipation.